Adsorption Thermodynamics and Kinetics of Mancozeb onto Poly--toluidine Th(IV) Phosphate — a Nano-composite Cation-exchanger — and its Application as a Mancozeb-sensitive Membrane Electrode - Asif Ali Khan; Anish Khan (Adsorption Science & Technology)
A newly-synthesized poly- o -toluidine Th(IV) phosphate nano-composite cation-exchanger was employed as an adsorbent to study the adsorption thermodynamics and kinetics of Mancozeb from aqueous media. Some parameters such as the Freundlich constants, the thermodynamic equilibrium constant (K 0 ), the standard free energy change (ΔG 0 ), the standard enthalpy change (ΔH 0 ) and the standard entropy change (ΔS 0 ) were determined. Thermodynamic analysis revealed that the adsorption of Mancozeb onto poly- o -toluidine Th(IV) phosphate was exothermic, spontaneous and decreased as the temperature was increased from 25 °C to 45 °C. A pesticide-sensitive membrane electrode was fabricated using poly- o -toluidine Th(IV) phosphate as an electro-active composite material. Its sensitivity towards Mancozeb was monitored.